Shedding light on risk: Seroprevalence of Q fever among farm animals and workers in Ecuador - Guerrero-Freire, Mónica Salomé; Ledesma, Yanua; Echeverria, Gustavo; Blanco, Federico Carlos; Waard, Jacobus H. de (Elsevier, 2025)
Q fever, caused by the bacterium Coxiella burnetii, is a zoonotic disease that has been largely overlooked despite presenting significant risks to both animal and public health. Although well studied in some countries, in most countries in Latin America, there's a lack of information on C. burnetii infection, its prevalence, and its impact on both livestock and human populations. To address this gap, we conducted a serosurvey among farm workers, cattle, sheep, and dogs on two dairy farms in Ecuador using a commercial ELISA kit. Additionally, we conducted a case-control study in cattle to investigate the association between C. burnetii infection and abortion. The findings revealed that 18 % of farm workers, 30 % of dogs, 25 % of cattle and 2 % of sheep tested positive for Q fever antibodies. Interestingly, no significant association between C. burnetii infection and abortion was observed in cattle (p < 0.05) but a high Neospora caninum seroprevalence indicated a strong link to abortion due to this parasite infection. The results highlight the presence of Q fever in both humans and animals on the surveyed farms, with farm dogs showing the highest seroprevalence. A point of concern arises from the significant prevalence of antibodies detected among farm workers, suggesting a potential history of unconfirmed symptomatic respiratory infections caused by a C. burnetii infection. However, further investigations are necessary to better understand the infection dynamics and its potential implications for public and animal health.